1996
DOI: 10.1016/0028-3932(95)00159-x
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions and disease characteristics in Parkinson's disease

Abstract: Abstract-In the present study, we investigated the association of two executive functions with disease characteristics in Parkinson's disease (PD), especially with severity of motor symptoms. We operationalized two executive functions, viz. fluency and cognitive shifting, each in a number of tests with heterogeneous materials, but with an identical format. We calculated the correlations between test performance and disease characteristics, including the factor scores of the Unified Parkinson's Disease Rating S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 49 publications
0
17
1
Order By: Relevance
“…For example, Van Spaendonck and colleagues (1996) evaluated executive cognitive functions and found that while tasks that involved cognitive shifting were correlated with the severity of motor impairment as measured by the Unified Parkinson's Disease Rating Scale (UPDRS), no relationship was observed between fluency tests and the UPDRS score (Van Spaendonck, Berger, Horstink, Buytenhuijs, & Cools, 1996). In line with this, Locascio and colleagues (2003) showed that while keeping age and disease duration constant, 13 out of 14 cognitive measures they tested were positively related to the extent of clinical disability as measured by the Hoehn and Yahr scale.…”
Section: Disease Severitymentioning
confidence: 97%
“…For example, Van Spaendonck and colleagues (1996) evaluated executive cognitive functions and found that while tasks that involved cognitive shifting were correlated with the severity of motor impairment as measured by the Unified Parkinson's Disease Rating Scale (UPDRS), no relationship was observed between fluency tests and the UPDRS score (Van Spaendonck, Berger, Horstink, Buytenhuijs, & Cools, 1996). In line with this, Locascio and colleagues (2003) showed that while keeping age and disease duration constant, 13 out of 14 cognitive measures they tested were positively related to the extent of clinical disability as measured by the Hoehn and Yahr scale.…”
Section: Disease Severitymentioning
confidence: 97%
“…An early study reported that executive dysfunction in PD was not correlated with motor function (Van Spaendonck et al, 1996). As mentioned above, the Norwegian ParkWest study noted mild cognitive impairment among 196 non-demented patients with PD (Aarsland et al, 2009) compared to age-matched controls.…”
Section: Spectrum Of Cognitive Dysfunction In Pdmentioning
confidence: 99%
“…These processes typically involve the frontal lobe (Fuster, 2008). These impairments are revealed using classic tests of executive function (Van Spaendonck et al, 1996) including verbal fluency, abstract reasoning, picture completion, Stroop performance (Aarsland et al, 2011), and performance on the Tower-of-London task (Foltynie et al, 2004). Executive functions can include inhibitory control (Stuss et al, 2005; Picton et al, 2006) which may be impaired in PD (Wylie et al, 2010; Mirabella et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, PD-related executive dysfunction is not directly correlated with motor dysfunction (Van Spaendonck et al, 1996), although it has been linked with gait-disturbance (Wylie et al, 2012). Dopaminergic therapy does not reliably improve executive dysfunction in high-functioning (Pascual-Sedano et al, 2008) or moderate PD patients (Morrison et al, 2004) and potentially can have detrimental effects (Cools et al, 2001; Cools and D’Esposito, 2011).…”
Section: Introductionmentioning
confidence: 99%